2010
DOI: 10.1002/jcc.21489
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of an energetic fullerene derivative

Abstract: A self-consistent estimation method for the thermochemical properties of N-methyl-3-(2',4',6'-trinitrobenzene)-fulleropyrrolidine (MTNBFP) is presented. This method is based on enthalpy of formation (Delta(f)H(m)(minus sign in circle)) and enthalpy of combustion obtained from BLYP/DNP calculations of the total energies and frequencies for MTNBFP. The enthalpy of formation was calculated by an optimized set of isodesmic reactions given the available experimental Delta(f)H(m)(minus sign in circle) of relative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It has been calculated that the enthalpy of formation of Cp-5 is 2782.2 kJ mol −1 , while its detonation velocity and pressure are 3282 km s −1 and 4.443 GPa, respectively. 112 Upon complete combustion, the total heat of combustion for Cp-5 is 2.17 × 10 5 kJ mol −1 due to its high carbon content. It seems that this compound may not be useful as the main ingredient of an explosive or a propellant but it might be a good additive for heat-generating energetic compositions.…”
Section: Ems Based On Functionalized C 60 Fullerenementioning
confidence: 99%
“…It has been calculated that the enthalpy of formation of Cp-5 is 2782.2 kJ mol −1 , while its detonation velocity and pressure are 3282 km s −1 and 4.443 GPa, respectively. 112 Upon complete combustion, the total heat of combustion for Cp-5 is 2.17 × 10 5 kJ mol −1 due to its high carbon content. It seems that this compound may not be useful as the main ingredient of an explosive or a propellant but it might be a good additive for heat-generating energetic compositions.…”
Section: Ems Based On Functionalized C 60 Fullerenementioning
confidence: 99%
“…The self-consistent-field (SCF) tolerance was set to be 1 × 10 –5 Ha. Compounds that are smaller in size and inorganic in nature having similar reactive features to this work have been extensively studied with success previously in our group using comparable hybrid methodologies. The accuracy of the BLYP/DNP level of theory has been documented for the reaction energetics and thermochemistry of similar organic and biopolymers. …”
Section: Computational Methodologymentioning
confidence: 96%
“…A numerical basis set of double zeta quality plus polarization functions (DNP) was used, which allowed for the truncation of the numerical integration, thus increasing the computational efficiency. We selected the BLYP/DNP level of theory after assessing its performance in studying reaction energetics and predicting thermochemistry for lignin model oligomeric species in our previous two studies , as well as the reported use of BLYP/DNP for studying organic compounds with similar objectives. The Tkatchenko–Scheffler (TS) method was used as the dispersion correction to include nonbonded interactions . Using the lowest energy conformation for the reactant, geometry optimization was done at the BLYP/DNP level where the convergence tolerances were 2× 10 –5 Hartree for the total energy, 0.004 Ha/Å for the maximum force, and 0.005 Å for the maximum displacement.…”
Section: Computational Methodologymentioning
confidence: 99%